Penerapan metode gallery walk terhadap hasil belajar recount text siswa sma kelas x ipa - Mei Susiatun (Universitas Sebelas Maret, 2020)
The purpose of this study is to determine the student learning outcomes taught usingthe Gallery Walk method on recount text material in Science X Class Academic Year2019/2020. This research is an experimental research with one-group PreTest-PostTest Design with the study population students of class X IPA consisting of 66 students in 2 classes. The sampling technique is purposive sampling. The sample is 32 class X IPA 2 students. Data collection technique is multiple choice test instrument totaling 15 items, each item has 5 options. Data analysis technique uses descriptive statistical analysis. The result of the study is that the average score data before applying Gallery Walk is 55,92 and after applying it is 69,90. The influence of Gallery Walk method on student learning outcomes in this study is 13,98.(=69,90-55,92) and students who had reached KKM (75) as much as 29,03% compared with the previous as much as 6,45%. So it can be concluded that the use of Gallery Walk method can increase student learning outcomes of the recount text material on Science X students.